Determination of visible particles in parenteral dosage forms and ophthalmic dosage forms - Yu. V. Olefir; T. N. Bokovikova; L. A. Stronova; E. P. Gernikova; L. I. Mitkina; S. A. Manaeva; Yu. B. Purim; A. V. Pichugin (Регуляторные исследования и экспертиза лекарственных средств)
The present article describes the approaches to the choice of methods for assessing the content of visible particles in parenteral and ophthalmic dosage forms, recognized in general pharmacopoeia monograph «Visible particles in parenteral dosage forms and ophthalmic dosage forms», as well as a special approach to the assessment of visible particles in individual preparations according to the batch volume, package type, the amount of drug in a package, drug nature etc., requiring unusual conditions and evaluation criteria.